Hieronymi Quaestiones Hebraicae in Libro Geneseos - Lagarde, Paul Anton de (Analecta Gorgiana, 2009)
Written in the scholarly Latin of his day, Lagarde considers in this brief study the questions Jerome raises on the Hebrew of the book of Genesis. In an abridged commentary form, Lagarde follows the questions in the order in which the book of Genesis presents the material. Beginning with the creation, Lagarde skips along to the phrases of Jerome's text that raise questions and provides his insights about them. Presuming that the reader of the Vulgate will understand the Latin of the original, the comments on the material are likewise written in Latin